Portraits of spiritual authority : religious power in early Christianity, Byzantium, and the Christian Orient - Drijvers, Jan Willem.; Watt, J. W. (Religions in the Graeco-Roman World, 1999)
This volume deals with several figures of spiritual authority in Christianity during late antiquity and the early middle ages, and seeks to illuminate the way in which the struggle for religious influence evolved with changes in church and society. A number of literary portraits are examined, portraits which, in various literary genres, are themselves designed to establish and propagate the authority of the people whose lives and activities they describe. The sequence begins with visionary and prophetic figures of the second and third centuries, proceeds through several testimonies from the fourth century to the power of holy persons, moves on to Syriac portraits of the fifth to seventh centuries, and ends with the demise of the authority of the holy man in the eighth.